ANALISA SETTING PROTEKSI OVER CURRENT RELAY (OCR) PADA GENERATOR 30 MW UNIT PLTA POSO PT. POSO ENERGY - Ramadani, Angger; Rahman, Yuli Asmi; Masarrang, Maryantho; Kali, Agustinus; Pirade, Yulius Salu (Foristek, 2024)
To ensure that the performance of the protection system is still good or not in terms of protection, calculations and adjustments must be made to the safety relay settings, especially the over current relay. In the research, analysis of the over current relay protection settings on the 30 MW generator at the Poso 1 PT PLTA unit. Poso Energy obtained that the maximum load current data on the generator was 2042 A, while the calculation results obtained were 2041.7 A. For the relay (top) operating time in the specification data, the value was 1.4 s, while in the calculation results it was 1.3 s. And for the setting current (Is) in the specification data the value is 4.7 A, whereas in the calculation results it is 4.28 A. Over current relay (OCR) or over current relay is an auxiliary relay from the differential relay, the over current relay is used to secure the generator of the overcurrent in the Poso 1 PLTA is PCS-985GE-EN-H2-110V-5A. In the specification data, the TMS value is 0.15 s, while in the calculation results it is 0.14 s. This means that data in the field is slower to protect components from interference by 0.01 s. However, overall the overcurrent relay settings on the generator at the Poso 1 PLTA are still in good condition.